24 Primary and secondary ICD implantation in adult congenital heart disease patients from 2006 to 2020: a single centre experience. (4th June 2021) - Hickman, Sally; Birkitt, Linda; Oliver, James; English, Kate; Slater, Tom; Sengupta, Anshuman
Abstract : Introduction: Adults with congenital heart disease are at risk of developing sustained ventricular arrhythmias, due to the underlying structural heart disease, myocardial scarring from previous cardiac surgery, or failing systemic or subpulmonary ventricles. Therefore, there are a number of potential indications for ICD implantation, both primary and secondary. Here we describe the rates of ICD implantation over the last 15 years in adults with congenital heart disease in our centre. Methods: A local database of all patients with congenital heart disease having undergone ICD implantation was interrogated to determine details of patients with new ICD implants from the last 15 years. Information on demographics, date of initial corrective cardiac surgery, date of ICD implant and indication for ICD were obtained. Results: 113 patients were identified, of which 65 (58%) underwent primary prevention device implantation and 48 (42%) underwent secondary prevention device implantation. 41 patients undergoing ICD insertion were female (36%) and 72 were male (64%). An overall downtrend in numbers of ICDs being implanted per year over the last 15 years was seen ( figure 1A ), the fall in the last 5 years being especially pronounced ( figure 1B ) . There was a minor increase in the proportion of ICDs implanted for primary prevention in 2015 to 2020 (63%) compared to 2006 to 2015 (57%). Time between initial corrective surgery and ICD implantation was similar through 2006 to 2020. Between 2006 and 2015 the average number of years between surgery and ICD implant was 27 years for primary prevention and 23 years for secondary. In the last 5 years the average number of years between surgery and ICD implant was 23 years for both indications. Figures 2A and 2B show the underlying condition in those who had an ICD implanted over the 15 year period. These demonstrate a decline in ICD implantation for those with either Tetralogy of Fallot or Transposition of the Great Arteries (TGA and CCTGA) in the last 5 years compared with data from 2006-2015; 52% to 41%, and 30% to 22% respectively. The number of patients undergoing ICD implantation with 'Other' underlying congenital heart disease is shown to have increased from 18% of overall cases in 2006-2015, to 37% of overall cases in 2016 to 2020. Tables 1 and 2 detail the 'Other' conditions and the indication for device. Conclusions: Despite the number of ACHD patients in the population increasing significantly over the same time period, annual rates of ICD implantation in our centre have reduced over time, especially over the last 5 years. The reason for this decline may reflect historical improvements in cardiac surgical techniques and the timing of surgery, thereby resulting in preserved ventricular function and less ventricular scar. Close, regular follow up in the modern era will likely result in early detection and treatment of structural problems which might be expected to reduce the incidence of serious arrhythmia. Regular surveillance would also be expected to allow for earlier detection of non-sustained ventricular arrhythmia, resulting in the initiation of anti-arrhythmic therapy that might prevent or delay the need for an ICD. Conflict of Interest: None